2002
DOI: 10.5488/cmp.5.2.329
|View full text |Cite
|
Sign up to set email alerts
|

INTERPRETATION OF POTENTIAL INTERMITTENCE TITRATION TECHNIQUE EXPERIMENTS FOR VARIOUS Li-INTERCALATION ELECTRODES

Abstract: In this paper we compare two different approaches for the calculation of the enhancement factor W i , based on its definition as the ratio of the chemical and the component diffusion coefficients for species in mixed-conduction electrodes, originated from the "dilute solution" or "lattice gas" models for the ion system. The former approach is only applicable for small changes of the ion concentration while the latter allows one to consider a broad range of intercalation levels. The component diffusion coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…This approach is described in detail in a number of publications of the authors Levi et al [27,37,61,64,[80][81][82]. It is based on the microscopic Lattice gas model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach is described in detail in a number of publications of the authors Levi et al [27,37,61,64,[80][81][82]. It is based on the microscopic Lattice gas model.…”
Section: Resultsmentioning
confidence: 99%
“…At the analysis of calculation results according to the model equations, authors Levi et al in their works [27,37,61,64,[80][81][82] showed that the structure of materials with strong interparticle interactions (pronounced Bdouble phase behavior^with the long flat plateau on E,c dependence) produce an uncertainty of the C dif (x) function, which values are used for D calculation. Therefore, it is reasonable to carry out D determination in the materials having a extended domain of solid solution existence (sloped E,c dependence).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The usefulness of the new method for determination of the chemical diffusion coefficients in practical intercalation electrodes for rechargeable lithium batteries will be addressed in a separate paper [22]. Detailed reviews on the specific problems encountered in obtaining and interpreting PITT data related to various practical intercalation electrodes, but with no account of ohmic and kinetic effects, have been previously published [23,24].…”
Section: Introductionmentioning
confidence: 99%